Ekonomi Hijau dan Pemulihan Ekonomi : Strategi, Implementasi, dan Hambatan Global - Muh. Adzam (Dharma Ekonomi, 2024)
The concept of the green economy serves as a global strategy to address social, economic, and environmental crises. It involves the development, implementation, and evaluation of various approaches to promote sustainability, reduce poverty, and support vulnerable social groups. This study explores the role of the green economy in economic recovery and multilateral issues using a descriptive literature-based method. The findings suggest that implementing a green economy can drive national recovery and address global challenges. Policymaker collaboration and public support are crucial for ensuring a sustainable and environmentally healthy ecosystem for present and future generations.